THE INFLUENCE OF ORGANIZATIONAL CLIMATE, COMPENSATION AND COMPETENCE ON EMPLOYEE PRODUCTIVITY PT. JISS INDONESIA SEJAHTERA JAKARTA AREA - Erina Juliana Putri; Roni Faslah; Rizki Firdausi Rachmadania (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
In the current business landscape, organizations recognize that their success and sustainability are intricately tied to the performance and productivity of their employees. As such, numerous factors contribute to shaping employee productivity, including the organizational climate, compensation structures, and employee competence. This study aims to determine the effect of organizational climate, compensation and competence on the work productivity of employees of PT JISS Indonesia Sejahtera Jakarta area. This study was conducted for 3 months from June 2023 to August 2023. The research method used is the survey method with a sample size of 195 respondents chosen from a population of 382 employees through the application of the Slovin formula. All data were collected as primary data and processed utilizing SPSS version 26.0, followed by data analysis encompassing tests to validate the classical assumptions. Multicollinearity tests demonstrated tolerances and VIF values falling within acceptable ranges, thus confirming the absence of multicollinearity. The heteroscedasticity test indicated homoscedasticity for the variables. Multiple linear regression revealed a model linking organizational climate, compensation, and competence to work productivity. Hypothesis tests indicated that the combined influence of these factors was statistically significant, with t-tests confirming individual positive influences. The coefficient of determination indicated that 72.8% of work productivity variability can be attributed to organizational climate, compensation, and competence, while the remaining 27.2% is influenced by unexamined variables.